Yuppie kvetch? Work-life conflict and social class in Western Europe - Frances McGinnity; Emma Calvert (The Economic and Social Research Institute (ESRI), 2008)
Recent debates on time-use suggest that there is an inverse relationship between time poverty and income poverty (Aguiar and Hurst, 2007), with Hammermesh and Lee (2007) suggesting much time poverty is 'yuppie kvetch' or 'complaining'. Gershuny (2005) argues that busyness is the 'badge of honour': being busy is now a positive, privileged position and it is high status people who work long hours and feel busy. Is this also true of work-life conflict? This paper explores the relationship between work-life tension and social inequality, as measured by social class, drawing on evidence from the European Social Survey (2004). To what extent is work-life conflict a problem of the (comparatively) rich and privileged professional/managerial classes, and is this true across European countries? The countries selected offer a range of institutional and policy configurations to maximise variation. Using regression modelling of an index of subjective work-life conflict, we find that in all the countries under study, work-life conflict is higher among professionals than non-professionals. Part of this is explained by the fact that professionals work longer hours and experience more work pressure than other social classes, though the effect remains even after accounting for these factors. Country variation is modest, despite much variation in policies concerning work-life conflict. We consider other explanations of why professionals report higher work-life conflict and the implications of our findings for debates on social inequality.
Keywords: 330; work-life balance; social inequality; work pressure; comparative research; Western Europe; Zeitverwendung; Arbeitszeit; Freizeit; Soziale Lage; Westeuropa